Benign childhood epilepsy with centro-temporal spikes: correlation between clinical, cognitive and EEG aspects Epilepsia benigna da infância com pontas centrotemporais: correlação entre aspectos clínicos, eletrencefalográficos e cognitivos - Lineu Corrêa Fonseca; Glória Maria A.S. Tedrus; Elisabeth Marinelli de Camargo Pacheco; Marcela Fernanda Berretta; Amanda Augusta Campregher; Débora Macedo Costa (Arquivos de Neuro-Psiquiatria)
Benign childhood epilepsy with centro-temporal spikes (BECTS) is a form of epilepsy with no demonstrable anatomical lesion showing spontaneous seizure remission. During the active phase of the disease the children may show cognitive deficits. The objective of this study was to assess, in children with BECTS, the relationship between clinical-EEG aspects and performance in the school performance test (SPT), Raven's progressive matrixes test and the Wechsler Intelligence Scale for Children (WISC-III). Forty-two 7 to 11 year old children were included and the following tests carried out: anamnesis, neurological examination, electroencephalogram (EEG), SPT, Raven's test and WISC-III. The children with BECTS had normal IQ values but showed inferior performance in the SPT more frequently than "healthy" children, paired with respect to age and maternal scholastic level. There was moderate positive correlation between WISC-III results and the age when the seizures started and the educational level of the parents. On the other hand, aspects linked to the epileptic nature of BECTS, such as the number of seizures, time since last seizure and the number and lateralization of the centro-temporal spikes on the EEG, showed no correlation with the neuropsychological tests. A epilepsia benigna da infância com pontas centrotemporais (EBICT) é uma forma de epilepsia na qual não existem lesões anatômicas demonstráveis e há remissão espontânea das crises. Na fase ativa da epilepsia as crianças podem apresentar déficits cognitivos. O objetivo deste estudo foi avaliar, em crianças com EBICT, a relação entre aspectos clínico-eletrencefalográficos e o desempenho no teste de desempenho escolar (TDE), no teste das matrizes progressivas de Raven e na Escala Wechsler de Inteligência para Crianças (WISC-III). Foram incluídas 42 crianças de 7 a 11 anos de idade. Foram realizados: anamnese, exame neurológico, eletrencefalograma (EEG), TDE, teste de Raven e WISC-III. As crianças com EBICT tiveram valores normais de QI e apresentaram desempenho inferior no TDE mais freqüentemente que crianças "sadias" pareadas quanto à idade e à escolaridade materna. Houve correlação positiva moderada entre idade de início das crises e escolaridade dos pais com resultados do WISC-III. Por outro lado, aspectos ligados à natureza epiléptica da EBICT como número de crises, tempo decorrido da última crise, número e lateralidade das pontas centrotemporais ao EEG não mostraram correlação com os resultados dos testes neuropsicológicos.